AB1105 Barriers to Appointment Compliance and the Effect of Reminder Phone Calls on Clinic Show Rate at an Academic Lupus Clinic in the Underserved Community. (9th June 2015) - Kumthekar, A.; Johnson, B.
Abstract : Background: Appointment compliance is a nationwide problem with a higher prevalence in the underserved communities. For physicians, a no-show results in lost time, decreased efficiency, and higher use of resources. For patients, it results in dissatisfaction and reduced quality of care when they do not receive appropriate follow ups. Lupus patients are particularly vulnerable given the disease complexity and high morbidity and mortality due to such complications as lupus nephritis, neuropsychiatric lupus and pericardial and pleural effusions. Missing an appointment for a lupus patient can made the difference in terms of keeping the patient out of the hospital. The primary objective of this study was to identify major obstacles to appointment compliance in an underserved Lupus Clinic. Secondary objective was to assess appointment compliance after an intervention involving reminder phone calls. Objectives: The purpose of this study was to identify major obstacles to appointment compliance and to create an intervention to improve appointment compliance based on the initial assessment. Methods: During phase one from February-June 2014, we retrospectively assessed the appointment compliance at our Lupus clinic catering to the "low income" population with medicare/medicaid or no insurance. This was done using the Sorian based scheduling software and scheduled patients were confirmed to have attended clinic by verifying the provider's visit note. A survey was designed to understand barriers to lupus clinic visit in our patient population. The patient survey was implemented over a period of 6 weeks from July 1 2014 to August 12 2014 with a total of 43 responses. In phase 2, an intervention involving reminder telephone call 1-3 days prior to the visit was planned. The intervention was implemented for 2 months and the results were analyzed after completion of intervention period. Results: During phase one, 288 lupus patients were analysed with an average compliance of 59%. The most common reason for missed appointment from our survey was that the patient forgot about the appointment which 46.5% of responders mentioned. 11.6% said that the appointment was cancelled by the office or they did not have an appointment before they left the clinic. During phase two of the study, appointment compliance was 75% after reminder phone. Conclusions: In a multidisciplinary specialized lupus clinic catering to underserved "low income" population we found that appointment compliance is more likely related to lack of appointment reminders. Our data suggests that reminder phone calls significantly improves compliance in Lupus patients which in turn will help in reducing hospitalizations. References: Capko, J. The Price You Pay for Missed Appointments. The Journal of medical practice management: MPM 22.6 (2007): 368. Husain-Gambles, M., et al. Missed Appointments in Primary Care: Questionnaire and Focus Group Study of Health Professionals. The British journal of general practice: the journal of the Royal College of General Practitioners 54.499 (2004): 108-13. Disclosure of Interest: None declared